Me ajudem nessa questão.
Anexos:
![](https://pt-static.z-dn.net/files/db8/c25b35646a3128c1febe68651ba3b9d9.png)
Soluções para a tarefa
Respondido por
1
f(x) = x² - 4x + 7
f(0) = 0² - 4.0 + 7 = 0 -0 + 7 = 7
f*-3) = -(3)³ -4.(-3) + 7 = 9 +12 + 7 = 21 + 7 = 28
f(2) = 2² - 4.2 + 7 = 4 - 8 + 7 =11 - 8 = 3
f(10) 10² - 4.10 + 7 = 100 - 40 + 7 = 60 + 7 = 67
(7, 28, 3, 67)
Letra C
f(0) = 0² - 4.0 + 7 = 0 -0 + 7 = 7
f*-3) = -(3)³ -4.(-3) + 7 = 9 +12 + 7 = 21 + 7 = 28
f(2) = 2² - 4.2 + 7 = 4 - 8 + 7 =11 - 8 = 3
f(10) 10² - 4.10 + 7 = 100 - 40 + 7 = 60 + 7 = 67
(7, 28, 3, 67)
Letra C
denizejvillein:
Muito obrigadaaa
Perguntas interessantes